KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 PADANG PANJANG - Suenti, Yolmi; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTThe purpose of this study is three. First, it describes the reading comprehension skills of the VII grade students of SMP Negeri 1 Padang Panjang. Second, describe the writing skills of the description text of grade VII students of SMP Negeri 1 Padang Panjang. Third, describe the correlation of reading comprehension text description with the description writing skills of grade VII students of SMP Negeri 1 Padang Panjang. This type of research is quantitative with descriptive methods. The design used in this study is a corelasinoal design. The population of this research is class VII students of Padang Panjang State Junior High School registered in the 2018/2019 school year, which is 192 students. The sample in this study was determined by proportional random sampling of 25% of the population, that is 48 students. The data of this study were in the form of scores on the reading comprehension test scores of the description text description and the scores on the writing of the description text skills. The data was obtained through two types of tests namely objective tests to measure reading comprehension text skills and performance tests to measure description text writing skills. Based on data analysis and discussion, three research results are obtained as follows. First, reading comprehension text skills of grade VII students of SMP Negeri 1 Padang Panjang are in good qualifications. This can be seen from the acquisition of an average of 81.35. Second, the description writing skills of grade VII students of SMP Negeri 1 Padang Panjang are in good qualifications. This can be seen from the acquisition of an average of 77.15. Third, there is a significant relationship between reading comprehension text description skills and description writing skills for grade VII students of SMP Negeri 1 Padang Panjang. Based on the results of this study, it can be concluded that there is a correlation between reading comprehension and description text writing skills with the description text of Grade VII students of SMP Negeri 1 Padang Panjang at n-1 degrees of freedom and a significant level of 95%. So, it was concluded that the higher the reading comprehension skills of students 'description texts, the higher the students' writing description text skills. Kata kunci: Keterampilan Membaca Pemahaman, Keterampilan                    Menulis, Teks Deskripsi, Korelasi